Mucinous Cystic Borderline Tumor of the Mesentery: A Case Report - Poudel, R.; Acharya, A.; Pokhrel, S.; Adhikari, S.K. (Kathmandu University Medical Journal, 2017)
Mucinous cystic neoplasms are rare tumors of uncertain histogenesis. They arise from the ovaries, pancreas, and other intra-abdominal sites but more unusually from the mesentery. They can present with abdominal pain, distension, or a palpable mass but are commonly an incidental finding. We present a case of a 33 year old female who presented with complain of pain abdomen for one-year duration. On Physical examination there was a palpable lump in right lumbar region extending to right iliac fossa. CT scan of abdomen and pelvis suggested the mass to be a Mesenteric Cyst. Enucleation of the cyst was done and histopathology report revealed Mucinous Cystic borderline tumor of the Mesentery.